Этнокультурные процессы на белорусско-украинском пограничье - Касперович, Г. (Народна творчість та етнографія, 2009)
The article is based on materials of a scientific project, realized by Byelorussian and Ukrainian ethnologists. During the elaboration of this project the main attention was paid to revelation of basic tendencies and factors of the ethnocultural processes at the frontier of Byelorussia and Ukraine.